2020
DOI: 10.1126/scitranslmed.aay2176
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of aquaporin-1 prevents myocardial remodeling by blocking the transmembrane transport of hydrogen peroxide

Abstract: Pathological remodeling of the myocardium has long been known to involve oxidant signaling, but strategies using systemic antioxidants have generally failed to prevent it. We sought to identify key regulators of oxidant-mediated cardiac hypertrophy amenable to targeted pharmacological therapy. Specific isoforms of the aquaporin water channels have been implicated in oxidant sensing, but their role in heart muscle is unknown. RNA sequencing from human cardiac myocytes revealed that the archetypal AQP1 is a majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 85 publications
1
43
0
Order By: Relevance
“…This increase in oxidative stress was attributed to inflammation, as well as to renal epithelial cell damage, by activation of NADPH oxidase [ 136 , 138 , 140 , 142 ] NOX2/NOX4-derived ROS [ 138 , 142 ]. Such an increase in oxidative stress was reported to activate nuclear factor-kappa B [ 141 ], as well as several mechanisms implicated in cell membrane ionic transporters, in addition to aquaporin 1 sensitive transmembrane transporter of hydrogen peroxide [ 136 , 143 , 144 ] and osmolyte sensor ( Figure 3 ). However, recent literature in the field showed that high -salt-sensitive hypertension is due, at least in part, to damage of the glycocalyx of both vascular endothelial [ 136 ] and vascular smooth muscle [ 20 ] cells.…”
Section: Implication Of Ros/rns In Na + Sensitive Hypertensionmentioning
confidence: 99%
“…This increase in oxidative stress was attributed to inflammation, as well as to renal epithelial cell damage, by activation of NADPH oxidase [ 136 , 138 , 140 , 142 ] NOX2/NOX4-derived ROS [ 138 , 142 ]. Such an increase in oxidative stress was reported to activate nuclear factor-kappa B [ 141 ], as well as several mechanisms implicated in cell membrane ionic transporters, in addition to aquaporin 1 sensitive transmembrane transporter of hydrogen peroxide [ 136 , 143 , 144 ] and osmolyte sensor ( Figure 3 ). However, recent literature in the field showed that high -salt-sensitive hypertension is due, at least in part, to damage of the glycocalyx of both vascular endothelial [ 136 ] and vascular smooth muscle [ 20 ] cells.…”
Section: Implication Of Ros/rns In Na + Sensitive Hypertensionmentioning
confidence: 99%
“…Bacopasides I and II extracted from the Indian medicinal herb water hyssop (Bacopa monnieri) differentially inhibited AQP1-mediated water and ion fluxes and reduced motility, invasiveness, and lamellipodial formation of HT29 colon cells [72,180]. Inhibition of AQP1 intrasubunit pores by Bacopaside II impaired stress-induced H 2 O 2 influx, protecting against hypertrophic heart disease in mouse and human cardiac models [54]. A Chinese herbal medicinal extract, compound Kushing injection, reduced growth and invasiveness of colon cancer, breast cancer, and glioblastoma cell lines and altered the expression of genes including AQPs [188]; however, specific actions on AQP functions remain to be defined.…”
Section: Pharmacological Modulators Of Aquaporinsmentioning
confidence: 99%
“…The full spectra of solutes permeable through AQP channels remain to be defined. In addition to water, AQP1 allows transport of CO 2 [52], H 2 O 2 [53,54], NO [55], and NH 3 [56]. Several classes of mammalian AQPs function as ion channels.…”
Section: Aquaporin Class Referencementioning
confidence: 99%
“…The inhibition of H 2 O 2 translocation, by the aquaporin 1 inhibitor bacopaside, resulted in the suppression of hypertrophic responses and fibrotic responses in vitro. The treatment of mice with a clinically approved extract containing bacopasides attenuated cardiac hypertrophy and fibrosis [ 92 ]. These results suggest that aquaporin is a promising target for the treatment of cardiac fibrosis as well as hypertrophy.…”
Section: Treatment Of Fibrosismentioning
confidence: 99%